Correction: Development of Novel Faster-Dissolving Microneedle Patches for Transcutaneous Vaccine Delivery. Pharmaceutics, 2017, 9(3), 27 - Akihiko Ono; Sayami Ito; Shun Sakagami; Hideo Asada; Mio Saito; Ying-Shu Quan; Fumio Kamiyama; Sachiko Hirobe; Naoki Okada (MDPI AG, 2017)
The authors wish to make a change to their published paper [1].[...]